2015
DOI: 10.15252/embj.201489478
|View full text |Cite
|
Sign up to set email alerts
|

NTR 1 is required for transcription elongation checkpoints at alternative exons in Arabidopsis

Abstract: The interconnection between transcription and splicing is a subject of intense study. We report that Arabidopsis homologue of spliceosome disassembly factor NTR1 is required for correct expression and splicing of DOG1, a regulator of seed dormancy. Global splicing analysis in atntr1 mutants revealed a bias for downstream 5 0 and 3 0 splice site selection and an enhanced rate of exon skipping. A local reduction in PolII occupancy at misspliced exons and introns in atntr1 mutants suggests that directionality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
86
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 70 publications
(102 reference statements)
10
86
1
Order By: Relevance
“…For example, the RNAPII elongation rate, which is under control of TEFs, influences the efficiency of splicing and polyadenylation events (Elkon et al, 2013;Saldi et al, 2016). In plants, the interplay between transcript elongation and mRNA processing has only recently become apparent, as exemplified by the connection of TFIIS and PAF1-C with splicing (Dolata et al, 2015;Li et al, 2016). We also observed that a range of splicing factors copurified with CstF77.…”
Section: Discussionmentioning
confidence: 69%
“…For example, the RNAPII elongation rate, which is under control of TEFs, influences the efficiency of splicing and polyadenylation events (Elkon et al, 2013;Saldi et al, 2016). In plants, the interplay between transcript elongation and mRNA processing has only recently become apparent, as exemplified by the connection of TFIIS and PAF1-C with splicing (Dolata et al, 2015;Li et al, 2016). We also observed that a range of splicing factors copurified with CstF77.…”
Section: Discussionmentioning
confidence: 69%
“…ChIP in the Arabidopsis AGO1:FLAG line using anti-FLAG antibodies. Data normalized to a CTD Ser-5 is an indication of enzyme pausing during transcription (Alexander et al, 2010;Dolata et al, 2015). Therefore, we performed the stress experiments in the cpl1-7 mutant.…”
Section: Cpl1 Influences the Mir161 And Mir173 Expression In Responsementioning
confidence: 99%
“…ChIP was performed as previously described in Dolata et al (2015) using 2 mg of each antibody per IP: anti-RNAPII (AS11 1804; Agrisera), anti-AGO1 (AS09 527; Agrisera), and 30 mL of ANTI-FLAG M2 Magnetic Beads (SigmaAldrich). The RNase+ nuclear extract sample was treated with 2.5 mg of RNase A (Thermo Fisher Scientific) during IP.…”
Section: Chipmentioning
confidence: 99%
“…Transcription factor (TF)IIS knockout and TFIIS dominant-negative mutation lead to the slowdown of PolII elongation, which enhances proximal splice site selection on DOG1. In contrast, mutation of the spliceosome cofactor AtNTR1, which increases the rate of PolII elongation, results in the selection of distal splice sites (14). In addition to changes in DOG1 splice site selection, tfIIs and atntr1 mutants display low DOG1 expression and consequently a weak seed dormancy phenotype (14)(15)(16).…”
mentioning
confidence: 99%
“…In contrast, mutation of the spliceosome cofactor AtNTR1, which increases the rate of PolII elongation, results in the selection of distal splice sites (14). In addition to changes in DOG1 splice site selection, tfIIs and atntr1 mutants display low DOG1 expression and consequently a weak seed dormancy phenotype (14)(15)(16). Other known factors required for high DOG1 expression include the histone H2B ubiquitin transferases HUB1 and HUB2 (17),…”
mentioning
confidence: 99%